SUBGRAIN-SCALE DECOUPLING OF RE AND 187OS AND ASSESSMENT OF LASER ABLATION ICP-MS SPOT DATING IN MOLYBDENITE - Stein H.; Scherstén A.; Hannah J.; Markey R. (My University, 2003)
Reproducibility of Re-Os molybdenite ages depends on sample size and homogeneity, suggesting that Re and Os are decoupled within individual molybdenite crystals and do not remain spatially linked over time. In order to investigate the Re-Os systematics of molybdenite at the subgrain (micron) scale, we report LA-ICP-MS Re-Os ages for an Archean molybdenite crystal from Aittojärvi, Finland, analyzed in situ in a white aplite matrix. A related Aittojärvi molybdenite (A996D), in the form of a very fine-grained mineral separate, is used as one of our in-house NTIMS standards, and thus its age of 2760 ± 9 Ma is well established. Measurements of (187Re + 187Os)/185Re on micron scale spots along 200 μm traverses across the crystal yield a wide range of ages demonstrating that, in this case, microsampling of molybdenite does not produce geologically meaningful ages. Experimentation with mineral separations and sample size over a 7-yr period predicted that this would be the outcome. We suggest that 187Os is more likely to be the mobile species, based on its charge and ionic radius, and that 187Os becomes decoupled from parent 187Re with time on the micron and larger scale. Incompatible charge and ionic radius for Os ions formed during reduction of molybdenite-forming fluids may explain the widely observed absence of common (initial) Os in molybdenite. Geologically accurate ages for molybdenite can only be obtained for fully homogenized crystals (or crystal aggregates) so that any post-crystallization 187Re-187Os decoupling is overcome.
Keywords: Molybdenite